Essential role of Ca(2+)-binding protein 4, a Ca(v)1.4 channel regulator, in photoreceptor synaptic function - Haeseleer, Françoise (2004)
CaBP1–8 are neuronal Ca(2+)-binding proteins with similarity to calmodulin (CaM). Here we show that CaBP4 is specifically expressed in photoreceptors, where it is localized to synaptic terminals. The outer plexiform layer, which contains the photoreceptor synapses with secondary neurons, was thinner in the Cabp4(−/−) mice than in control mice. Cabp4(−/−) retinas also had ectopic synapses originating from rod bipolar and horizontal cells that extended into the outer nuclear layer. Responses of Cabp4(−/−) rod bipolars were reduced in sensitivity about 100-fold. Electroretinograms (ERGs) indicated a reduction in cone and rod synaptic function. The phenotype of Cabp4(−/−) mice shares similarities with that of incomplete congenital stationary night blindness (CSNB2) patients. CaBP4 directly associated with the C-terminal domain of the Ca(v)1.4 α(1)-subunit and shifted the activation of Ca(v)1.4 to hyperpolarized voltages in transfected cells. These observations indicate that CaBP4 is important for normal synaptic function, probably through regulation of Ca(2+) influx and neurotransmitter release in photoreceptor synaptic terminals.